Application of Distributed Web Crawlers in Information Management System (Informatica, 2018)
In the Internet era, cloud data and big data constantly develop, and Internet has become the main platform for enterprises and individuals to release information. As a result, a large amount of data generates, and people spend more energy on finding information that they want. The desire for accurately acquiring information needed becomes increasingly stronger. This study designed a distributed web crawlers system based on Hadoop and used it to do large-scale information management. The simulation experiment verified that the system could operate stably in information management system, which offers a reference for the application of distributed web crawlers in information management system.